Pelatihan Pemanfatan Quick Responde Code Technology dalam Pengembangan Media Pembelajaran - Anjani, Dewi; Novianti, Desi; Sadikin Wear, Ali (Institut Teknologi dan Bisnis Riau Pesisir, 2021)
Revolution 4.0 resulted in teachers having to continue to improve their abilities, especially in making learning media. Learning media is one of the teacher's tools to transfer knowledge to students. With the suitable media, the level of student understanding of the lesson will increase. During this pandemic, the learning method used is online. Teachers only provide material in the form of files in document format. Giving such learning materials makes students less interested in learning which causes a decrease in understanding of the material. From these problems, we need a learning media that can make students understand the material, which gives students enthusiasm in learning, namely by changing the learning media used today. One of the learning media that can increase students' interest in learning is interactive media, such as QR Code technology. For this reason, teachers need knowledge and understanding of making learning media using QR codes. To support this, the school held community service activities. The activity aims to introduce and provide training on QR Code Technology in the Development of Learning Media at SDN 15 Pal Merah, West Jakarta, so learning is more exciting and interactive.